Attachment of foodborne pathogens to banana (Musa sp.) leaves - Chua, P.; Dykes, Gary (2013)
Fresh produce, and in particular minimally processed leafy green vegetables, have been recognized as a source of transmission for foodborne pathogens of animal origin. In South-East Asian and other cultures the leaves of the banana plant (Musa sp.) are widely used as food wrappings or as serving plates because of their waxy surfaces and represent a largely uninvestigated leafy green product. This study was undertaken to quantify the attachment of two strains of each of the three bacterial foodborne pathogens Staphylococcus aureus, Salmonella enterica and Escherichia coli to the top side and underside of banana leaf surfaces. All bacteria tested attached to banana leaves at levels in the range of 3.5-4.5 cfu/cm2. Differences in attachment to leaves between strains were apparent. Most notably both Salmonella strains attached to the top side of leaf surfaces in significantly (p < 0.05) lower numbers than two (one E. coli and one S. aureus) of the other four strains. Furthermore, the two S. aureus strains attached to the undersides of leaves in significantly (p < 0.05) lower numbers than to the top side of leaves. Despite the waxy nature of the banana leaf surfaces the bacteria tested were capable of attaching to them in numbers equivalent to the attachment of bacterial pathogens to other leafy green produce. © 2013 Elsevier Ltd.